Comparison of model order reduction methods for optimal sensor placement for thermo-elastic models*. Issue 3 (4th March 2019) - Benner, Peter; Herzog, Roland; Lang, Norman; Riedel, Ilka; Saak, Jens
ABSTRACT: In this article an optimal sensor placement problem for a thermo-elastic solid body model is considered. Temperature sensors are placed in a near-optimal way so that their measurements allow an accurate prediction of the thermally induced displacement of a point of interest (POI). Low-dimensional approximations of the transient thermal field are used which allows for efficient calculations. Four model order reduction (MOR) methods are applied and subsequently compared with respect to the accuracy of the estimated POI displacement and the location of the sensors obtained.